2017
DOI: 10.1002/jclp.22442
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Social Support Postincarceration: Results From a Pilot Randomized Controlled Trial

Abstract: This study advances research on intervention dosage, potency, and measurement considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…However, a recent study evaluating the efficacy of a reentry intervention focused on social support found an inverse relationship between age and the amount of positive supportive behaviors reported in the individual’s social network (Pettus-Davis et al, 2016). Given these mixed findings, further research that follows longitudinally the relationships between gender, age, and perceived and experienced social support within a larger sample of reentering prisoners is worth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study evaluating the efficacy of a reentry intervention focused on social support found an inverse relationship between age and the amount of positive supportive behaviors reported in the individual’s social network (Pettus-Davis et al, 2016). Given these mixed findings, further research that follows longitudinally the relationships between gender, age, and perceived and experienced social support within a larger sample of reentering prisoners is worth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RCTs and other evaluative studies that examine the effectiveness of social network interventions in forensic psychiatric populations are scarce. One pilot RCT that compared a short group social support intervention with a general re-entry service among a small sample of recently released prisoners, found no statistically significant group effects for social support, cognitions, substance use and recidivism [42]. However, larger sample sizes are recommended to reliably investigate the effectiveness of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intervention comprised of a short intervention (i.e. 10 week training), while researchers emphasize that social support interventions for forensic psychiatric patients should be long lasting in order to find significant effects [27,42]. An evaluative study of a social support intervention among mentally ill prisoners during and after incarceration found a significant positive association with quality of life, but no significant association with criminal recidivism or psychiatric hospitalisation [43].…”
Section: Introductionmentioning
confidence: 99%
“…This approach also aligns with many pre-colonial Indigenous concepts of justice (Dickson-Gilmore & LaPrairie, 2005;Napoleon & Friedland, 2015). For example, studies have highlighted that positive relationships and community engagement can increase parole adherence and reduce substance use (Pettus-Davis et al, 2017;Skeem et al, 2009); relationships with friends, families, and community can improve mental, behavioural and physical health outcomes post-release (Binswanger et al, 2012;Skeem et al, 2009); and sustained positive social support both within and outside prison walls can reduce recidivism (Pettus-Davis et al, 2017;Rocque et al, 2013;Wright & Cesar, 2013). The CSC currently addresses social bonds and community engagement through contracts with community organizations, such as the Elizabeth Fry and John Howard Societies, both of which support justice-involved persons and their families, including Indigenous-focused supports (Elizabeth Fry Society of Greater Vancouver, 2019; John Howard Society of British Columbia, n.d.).…”
Section: Introductionmentioning
confidence: 99%